Methodology of Classical Usuli Texts: A Critical Appraisal of Taj al-Subki’s Jamʿ Al-Jawami' - al-Hudawi, Mohamed Jabir Ali; Babu Sahib, Hikmatullah (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
Classical contributions are said to be the major source for contemporary studies of uṣūl al-fiqh. However, their linguistic nuances and stylistic methodologies are foreign to many contemporary researchers which makes any meaningful discourse an onerous and often arduous task. In this article, an attempt is made to explain the methodology employed by Tāj al-Dīn al-Subkī, an eminent 8th/14th Century jurisprudent, in his uṣūlī text Jamʿ al-Jawāmiʿ. The text has been selected, for its wide reception and great impact on the later development of uṣūl al-fiqh, as a model for the uṣūlī matn genre. It is hoped that the article will generate more interest in understanding juristic jargon and its usages in elucidating the principles of Islamic Jurisprudence. By offering a comprehensive analysis of the methodology intrinsic to classical uṣūlī works, with "Jamʿ Al-Jawāmiʿ" as the primary focus, this article endeavors to enhance comprehension of how classical scholars tackled and elucidated matters of Islamic law. The study not only sheds light on the intellectual heritage of Islamic jurisprudence but also serves as a valuable resource for understanding the evolving nature of legal thought within the Islamic tradition.